2021
DOI: 10.2131/jts.46.329
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine prevents breast cancer growth by targeting neuronatin to inhibit nerve fibers formation

Abstract: Lidocaine has been shown to inhibit the invasion and metastasis of breast cancer, but the mechanism still remains unclear. This study explored the relationship between lidocaine and circulating seeding of breast cancer cells from the perspective of nerve fiber formation. The cell lines MDA-MB-231 and 4T1 were subcutaneously inoculated in mice to simulate the tumor self-seeding by circulating cancer cells. Lidocaine was used to treat these mice and tumor growth was observed. Silver staining was performed to obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 38 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that local anesthetics are toxic to multiple cancer types. Tu et al Reported that lidocaine could prevent breast cancer growth by targeting neuronatin to inhibit nerve bers formation [21]. Xu et al found that lidocaine could enhance the effects of chemotherapeutic drugs against bladder cancer [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that local anesthetics are toxic to multiple cancer types. Tu et al Reported that lidocaine could prevent breast cancer growth by targeting neuronatin to inhibit nerve bers formation [21]. Xu et al found that lidocaine could enhance the effects of chemotherapeutic drugs against bladder cancer [13].…”
Section: Discussionmentioning
confidence: 99%